Aplikasi Analisis Tes dalam Pembelajaran Fisika Berbantuan Bahasa Pemograman PHP - Fozza Andresta Putri; Gusnedi Gusnedi; Murtiani Murtiani (PILLAR OF PHYSICS EDUCATION, 2018)
The importance of evaluating school learning outcomes is one of the curriculum changes to achieve the successful implementation of the 2013 curriculum. evaluation is often done in terms of knowledge, so that learning outcomes tests can be used as evaluation tools. The tests which are used in the process of evaluating learning outcomes made by educators themselves or originated from educator guidebooks and question banks. Based on the results of interview with several educators, they have not believed yet that the questions given reflect the actual measuring instrument, so a problem analysis is needed. Therefore, making a test analysis application assisted with the PHP programming language can be a solution to this problem. This study aims to make a valid and practical test analysis application on physics learning assisted by a PHP programming language. Based on the results of the research that has been done, the conclusion of this study is the application of test analysis has been produced on physics learning assisted by a very valid PHP programming language with an average of 81 and very practical according to some educators with an average of 88.8.